新加坡和马来西亚华文书局的灭亡或转机 ：谈大众书局的困境与转型 = The extinction or turnaround of Chinese bookstores in Singapore and Malaysia : a study of Popular Bookstore’s crisis and its transformation - 黄琪雯 Ng, Qi Wen (2019)
本论文通过于1924年在新加坡创立的大众书局，探讨九十五年以来在新加坡和马来西亚不同时期政治变革影响下的转变，并进一步探讨现今社会书局存在的必要性和其意义。20世纪初，大量中国人民移民至新马，华人的侨民意识浓厚，华文教科书和书籍的需求大量增加，华文书局达到鼎盛时期。而世界书局（大众书局前身）不仅售卖从中国引进的教材，亦开始出版本地教科书，敢于创新的作风使世界书局奠定了基础。1942年二战爆发，许多书局被迫关闭，惟世界书局由一些老员工以售卖文具和库存的方式继续营业。战后，英殖民政府为防止共产思想流入而全面禁止来自中国大陆的书籍，世界书局将业务重心转变至出版，并筛选无共产意识的书籍供应给新加坡书业市场。而后新加坡和马来西亚走向自治独立，在教育上做出的本土化大幅度地影响了华文的地位，许多华文书局被迫结业。对此，大众书局化危机为转机，重新定位成“双语书局”，并塑造“一站式、多元化”的独特经营特色，转型后积极创新求变。大众集团不断扩展其业务，虽然遭到部分人的质疑，但努力在商业和理想间取得平衡，通过一系列建设为华文文化做出贡献。 This paper mainly discusses the ninety-five years transformation of Popular Bookstore in Singapore , which was established in 1924, under the influence of political reform in Singapore and Malaysia. The existence necessity and significance of bookstores in the present society are also further discussed in this paper. In the early 20th century, the number of Chinese immigrants continued to rise in Singapore and Malaysia. This situation has deepened the emigrant’s consciousness of Chinese and resulted in the increasing demand for Chinese textbooks and novels whereby the business of Chinese bookstores hit its high point during this period. The World Book Company, the predecessor of Popular Bookstore, not only sold imported Chinese textbook, but also published local textbooks. Its innovative spirit provided a solid basis to the foundation of the World Book Company. After the outbreak of World War II in 1942, many bookstores were forced to shut down. Nevertheless, the World Book Company still continued to operate its business through selling stationeries and books in the stocks by some seasoned employees. To prevent the spreading of communal thoughts from China during the post-war period, books from China were prohibited by the British colonial government. This has resulted in the shifting of World Book Company’s main emphasis to publication, providing solely of books without communal thoughts to Singapore booksellers’ market through careful sift. After the independence of Singapore and Malaysia, the localisation policy in education affected Chinese’s position in an extensive manner, followed by the forced declination of Chinese bookstores. In this regard, Popular Bookstore led a turnaround out of their crisis, in which they repositioned as a “bilingual bookstore” while shaping an unmatched “One Stop, Multiple Facets” characteristic of operation. Upon the transformation, innovation and changes were vigorously pursued with a never-ending business expansion. In spite of some remained sceptical towards the corporation, they tirelessly sought for the balance point between business and ideal to contribute to Chinese culture through diverse construction.